Parallels in practice: applying principles of research integrity and ethics in domestic violence fatality review (DVFR) - Cook, Elizabeth A. (Journal of family violence, 2023)
Purpose: Within the context of the big data society, new systems of data collection on domestic violence and abuse (DVA) have emerged. One such system is Domestic Violence Fatality Review (DVFR) which captures the various dimensions of gender, violence, and abuse required to form an evidence base for prevention. However, to date, there has been limited dialogue between practitioners and researchers about the ‘doing’ of DVFRs. Method: As DVFR systems vary by jurisdiction, we conducted a case study of Domestic Homicide Reviews (DHRs) in England and Wales. Applying the Research Integrity Framework (RIF) developed by the four Women’s Aid Federations in the United Kingdom (UK), this article examines both the practice of DHR and how it is utilised as data in research. Results: Informed by our situated perspectives as researchers and/or practitioners working in the field, our analysis demonstrates how undertaking DHR as a practitioner parallels collecting, accessing, and analysing data from DHRs as a researcher. Guiding principles are identified to help practitioners and researchers navigate the parallel challenges they confront and, critically, inform dialogue between practice and research. Conclusions: Implications for both professional practice and research are presented. To increase transparency and confidence, we argue that more attention should be afforded to the methodological and ethical issues inherent in both the practice of DHRs, and their utilisation as a source of data in research. While DHRs have differences to DVFRs in other jurisdictions, these findings also have implications for these other systems which will also be discussed.